2011
DOI: 10.1029/2010gb003859
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of ocean margin anaerobic processes on oceanic alkalinity budget

Abstract: Recent interest in the ocean's capacity to absorb atmospheric CO2 and buffer the accompanying “ocean acidification” has prompted discussions on the magnitude of ocean margin alkalinity production via anaerobic processes. However, available estimates are largely based on gross reaction rates or misconceptions regarding reaction stoichiometry. In this paper, we argue that net alkalinity gain does not result from the internal cycling of nitrogen and sulfur species or from the reduction of metal oxides. Instead, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 109 publications
(207 reference statements)
6
139
0
Order By: Relevance
“…Whereas this estimate agrees well with an independent estimation by Chen (2002) (16-31 Tmol yr −1 ), Hu and Cai (2011a) obtained a much smaller flux of 4-6 Tmol yr −1 . Note that all these three studies are based on different assumptions about the underlying processes that are generating A T .…”
Section: Benthic Alkalinity Release In the North Seasupporting
confidence: 73%
See 3 more Smart Citations
“…Whereas this estimate agrees well with an independent estimation by Chen (2002) (16-31 Tmol yr −1 ), Hu and Cai (2011a) obtained a much smaller flux of 4-6 Tmol yr −1 . Note that all these three studies are based on different assumptions about the underlying processes that are generating A T .…”
Section: Benthic Alkalinity Release In the North Seasupporting
confidence: 73%
“…Finally, based on modeled nitrogen and carbon budgets for the northwestern North Atlantic continental shelf, Fennel (2010) suggested that shelf sediments must be an important source of alkalinity. By contrast, Hu and Cai (2011a) estimated a much smaller mean alkalinity flux from global coastal sediments based on the upscaling of local denitrification and sulfate reduction rates. They concluded that sedimentary alkalinity fluxes are generally too low to significantly affect the alkalinity budget of the global ocean, but also stated that sedimentary anaerobic processes could be important on regional scales as an alkalinity release mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Net alkalinity gain is, however, only achieved during anaerobic processes that involve a permanent loss of remineralization products, e.g. through denitrification or pyrite burial (Hu and Cai 2003). Vegetation modifies sediment biogeochemical processes and, thus, affects the pH and alkalinity of pore waters.…”
Section: Regulation Of Seawater Ph In the Pre-disturbed Holocene Oceanmentioning
confidence: 99%